2006
DOI: 10.1111/j.1532-5415.2006.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Delirium within Three Days of Stroke in a Cohort of Elderly Patients

Abstract: Delirium occurred frequently in acute stroke patients aged 65 and older. Factors independently associated with delirium included old age, intracerebral hemorrhage, metabolic factors, prestroke dementia, initial GCS less than 15, and inability to lift both arms on admission. Patients with delirium had higher long-term mortality and a worse functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
113
4
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(138 citation statements)
references
References 16 publications
16
113
4
5
Order By: Relevance
“…In other studies, duration of delirium was in mean 4 days (Dostovic, Smajlovic, Sinanovic, & Vidovic, 2009;Mitasova et al, 2012) or 4.8 days (Oldenbeuving et al, 2011) and delirious episodes ≤24 hr were reported in 25% (Mitasova et al, 2012) to 46% (Sheng, Shen, Cordato, & Zhang, 2006). This phenomenon in patients with an acute stroke might be caused by cerebral dysregulation and associated with reduced perfusion, hypoxia, and disturbed neurotransmitters (Maldonado, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…In other studies, duration of delirium was in mean 4 days (Dostovic, Smajlovic, Sinanovic, & Vidovic, 2009;Mitasova et al, 2012) or 4.8 days (Oldenbeuving et al, 2011) and delirious episodes ≤24 hr were reported in 25% (Mitasova et al, 2012) to 46% (Sheng, Shen, Cordato, & Zhang, 2006). This phenomenon in patients with an acute stroke might be caused by cerebral dysregulation and associated with reduced perfusion, hypoxia, and disturbed neurotransmitters (Maldonado, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…The designs employed in the studies included in this review were prospective studies (n=11), retrospective studies (n=3) case controls (n=3), one cross sectional study, one pilot study of treatment intervention and one study which was described as "observational" (see table 2). A total of 12 studies reported applying established diagnostic criteria when assessing patients for delirium: Six (30%) studies applied DSM IV[2, [23][24][25][26][27], three (15%) studies applied DSM III-R [28][29][30], two studies applied DSM IV-R [31,32], and one (5%) study applied DSM III [33]. Three studies referred to "clinical assessment" but did not detail any diagnostic guidelines [34][35][36], and one study referred to the diagnosis of "disorientation" using a simple 3 point scale [37].…”
Section: Description Of Studies Included In This Reviewmentioning
confidence: 99%
“…There was no attempt in any of the studies to assess the suitability of using a generic delirium screening tool in acute stroke. A number of studies considered the challenge of using the above tools in acute stroke, as ten studies reported excluding patients with reduced consciousness [23,27,29,30,32,33,[36][37][38][39] and four studies excluded patients with aphasia [24,26,29,36]. Caeiro et al reported scoring zero in certain items of the DRS if patients had "language difficulties" [23,31,32], however, this term is somewhat vague.…”
Section: Diagnostic and Screening Tools Usedmentioning
confidence: 99%
See 2 more Smart Citations